"Não preciso, mas quero”: o mito da beleza em tempos de femvertising - Castro, Maria Luiza Pereira de (2020)
After decades of stereotyped media representations of women, femvertising emerges, an aspect of advertising that promotes female empowerment. With a proposal to deconstruct old aesthetic, behavioral patterns related to the female gender, it tries to fulfill its influential role in purchasing decisions. We observed the femvertising advertising“Rewind” that promotes the Make B. makeup line, created by “O Boticário”, in 2018. The research is justified by reflecting on how feminism's discourses are transformed into tools of neoliberalism, offered to her consumers. As a result of this reflection, we ask ourselves: as it is a discourse built to reach consumption, how does the commercial “Rewind” try to present a feminist discourse? What are the discourses pervaded in this advertising, with a view to promoting a possible awakening of the feeling of female empowerment? Can empowerment in women's lives be an advertising trend? To answer these concerns, we rely on Foucault's works, an archaeological and genealogical approach. In addition to this focus, we reflect on both the patriarchy and the distinctions between masculinity and femininity, present in the construction of the woman subject; we also discussed the Cultural Industry, focusing on the problem of the image of women; finally, we deal with the question of beauty, in the light of “The Myth of Beauty: how images of beauty are used against women”, Wolf (1991). In the end, we understand that, although femvertising does not necessarily promote the feminist cause, we think it may be a promising factor in advertising.